Carbon nanotube – Protamine hybrid: Evaluation of DNA cell penetration. (January 2016) - Caoduro, Cécile; Kacem, Raoudha; Boukari, Khaoula; Picaud, Fabien; Brachais, Claire-Hélène; Monchaud, David; Borg, Christophe; Boulahdour, Hatem; Gharbi, Tijani; Delage-Mourroux, Régis; Hervouet, Eric; Pudlo, Marc
Abstract: Carbon nanotubes (CNTs) represent a class of nanomaterials with important potential for biomedical and biotechnological applications. CNT based vectorization is an emerging approach to the transport of nucleic acid through cell membrane but limited by detachment of DNA and degradation process. To increase DNA internalization, it was proved that cationic functionalized CNT was essential. In such a way, protamine efficiently used in several transfection processes is a cationic protein which was never associated to CNT. We propose here a novel nanovector based on single-walled carbon nanotubes (SWCNT) functionalized by protamine. Our results based on qPCR methods clearly indicate that protamine-SWCNT/DNA hybrids were much more successful than ammonium-SWCNT/DNA hybrids to cross cell membrane and penetrate into cells. We also studied the cellular internalization mechanism of our complexes and showed that endocytosis was strongly involved. Finally, we proposed molecular dynamic simulations to understand the formation of the protamine-SWCNT/DNA complex and to extract the interaction responsible for its deliverance upon cell membrane.